Virological and Clinical Determinants of the Magnitude of Humoral Responses to SARS-CoV-2 in Mild-Symptomatic Individuals - Pradenas, Edwards; Ubals, Maria; Urrea, Víctor; Suñer, Clara; Trinité, Benjamin; Riveira-Muñoz, Eva; Marfil, Silvia; Ávila-Nieto, Carlos; Rodríguez de la Concepción, María Luisa; Tarrés-Freixas, Ferran; Laporte, Josep; Ballana, Ester; et al. (Frontiers in Immunology, 2022)
Background: Evidence on the determinants of the magnitude of humoral responses and neutralizing titers in individuals with mild COVID-19 is scarce. Methods: In this cohort study of mild COVID-19 patients, we assessed viral load (VL) by RT-qPCR at two/three time points during acute infection, and anti-SARS-CoV-2 antibodies by ELISA and plasma neutralizing responses at using a pseudovirus assay at day 60. Results: Seventy-one individuals (65% female, median 42 years old) were recruited and grouped into high viral load (VL) >7.5 Log10 copies/mL (n=20), low , VL ≤7.5 Log10 copies/mL (n=22), or as non-early seroconverters with a positive PCR (n=20), and healthy individuals with a negative PCR (n=9). Individuals with high or low VL showed similar titers of total neutralizing antibodies at day 60, irrespective of maximal VL or viral dynamics. Non-early seroconverters had lower antibody titers on day 60, albeit similar neutralizing activity as the groups with high or low VL. Longer symptom duration and older age were independently associated with increased humoral response. Conclusions: In mild SARS-CoV-2-infected individuals, the duration of symptoms and age (but not VL) contribute to higher humoral responses.